2003
DOI: 10.1002/bit.10811
|View full text |Cite
|
Sign up to set email alerts
|

Primmorphs from archaeocytes‐dominant cell population of the sponge hymeniacidon perleve: improved cell proliferation and spiculogenesis

Abstract: Marine sponges (Porifera) possess an extraordinary diversity of bioactive metabolites for new drug discovery and development. In vitro cultivation of sponge cells in a bioreactor system is very attractive for the sustainable production of sponge-derived bioactive metabolites; however, it is still a challenging task. The recent establishment of sponge primmorphs, multicellular aggregates from dissociated mixed-cell population (MCP), has been widely acknowledged to hold great promise for cultivation in vitro. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 24 publications
(49 reference statements)
2
41
0
1
Order By: Relevance
“…This is probably explained by the occurrence of apoptosis that counterbalances cell division . The only exception is the case of rapid growth recorded for primmorphs of the Chinese sponge Hymeniacidon perleve (Zhang et al, 2003b). The authors measured a ninefold increase of the cell mass within 7 days, but observed death of the primmorphs after 10 days.…”
Section: Primmorphsmentioning
confidence: 98%
“…This is probably explained by the occurrence of apoptosis that counterbalances cell division . The only exception is the case of rapid growth recorded for primmorphs of the Chinese sponge Hymeniacidon perleve (Zhang et al, 2003b). The authors measured a ninefold increase of the cell mass within 7 days, but observed death of the primmorphs after 10 days.…”
Section: Primmorphsmentioning
confidence: 98%
“…In order to produce sponge biomass that can be used as pharmaceutical potential, three-dimensional aggregates, and named primmorphs (multicellular aggregates from dissociated mixed-cell population) have been successfully used [5,6]. In H. perlevis, it has been proved that the addition of totipotent archaeocytes leads to be more stable primmorphs, thus suggesting a new method for the establishment of sponge cell culture in vitro [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical synthesis is too expensive and wild sponge collection has a negative impact on the environment and endangers the sustainable use of marine resources (according to convention on biological diversity rules). Sponge cultures have been assayed since the beginning of the last century (Moore, 1910); more recently, besides mariculture (in situ sponge culture; Pronzato et al, 1999;Duckworth and Battershill, 2003;Mendola, 2003), three methods for culturing sponges under controlled conditions have been used: explant culture (Osinga et al, 2001;de Caralt et al, 2003;Hoffmann et al, 2003;Nickel and Brü mmer, 2003), primmorphs (Mü ller et al, 1999;Zhang et al, 2003), and cells (Pomponi and Willoughby, 1994;Sipkema et al, 2003;De Rosa et al, 2003). However, most of these methods have encountered drawbacks with regard to survival and contamination (especially cell cultures) and/or growth rates (explants and primmorphs), and more research is required to make them suitable for scaling up sponge biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…In adult sponges, the cells closer to stem cells are archeocytes, which are able to differentiate in several cell types (e.g., oocytes, sclerocytes, pinacocytes). Some authors have performed cell culture from archeocyte enriched cell fractions, which presented active DNA synthesis, but failed to obtain continuous cell proliferation because of an early cell death (Pomponi and Willoughby, 1994;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%